Drobtinice prostega časa - Turk Niskač, Barbara (Etnolog. Nova vrsta (Ljubljana), 2020)
Taking as examples simply wandering around and the TikTok social network, the article analyses children's free time in relation to production and consumerism, with which the issue of moral discourse and social control can be connected. In the case of TikTok, the author shows how the borderlines between production and consumerism, as well as between free time and work, are erased. By contrast, wandering around is presented as an activity that until recently was part of the quotidian beyond social control.
Keywords: družbena omrežja; igra; komodifikacija; otroci; otroštvo; pohajanje; prosti čas; TikTok